FILSAFAT ILMU ISLAM: IMPLEMENTASI NILAI TAUHID DALAM AKTIVITAS EKONOMI ISLAM - Awara, Ganesta Putrya; Ali, Kayla Salsabilla; Nurfathan Pradana, Muhammad Farga; Nurhasanah, Yulia Intan (Taksasila Edukasi Insani, 2025)
This study examines the implementation of the value of tauhid as the philosophical foundation of Islamic economic activities from the perspective of Islamic philosophy of science. In contemporary economic practices, material orientation and profit maximization often marginalize ethical and spiritual values, resulting in injustice, exploitation, and moral crises. Islam, through the principle of tauhid, offers a comprehensive worldview that integrates theological, epistemological, and axiological dimensions in economic behavior. This research employs a qualitative method with a library research approach, analyzing classical and contemporary Islamic literature related to tauhid, Islamic philosophy of science, and Islamic economic principles. The findings indicate that tauhid functions not only as a theological belief but also as an epistemological and axiological framework that guides economic activities toward justice, responsibility, and social welfare. The implementation of tauhid in muamalah transforms economic activities into acts of worship and moral responsibility, emphasizing ethical conduct, prohibition of exploitation, and equitable distribution of wealth. However, the study also identifies challenges in applying tauhid-based values within modern economic systems due to globalization, technological complexity, and profit-oriented practices. Therefore, strengthening the internalization of tauhid is essential to realize an ethical, just, and sustainable Islamic economic system oriented toward falah.Keywords : Islamic Philosophy of Science, Tauhid, Islamic Economic Activities, Muamalah, Islamic Ethics